Ronda del Sinú Avenue: Spaces and meanings (2017)
OBJECTIVE: To understand the meaning assigned by citizens of Montería (Colombia) to Ronda del Sinú, considered a geo-urban construction which transformed the old space of Avenida Primera, one of the most important roads in the city of Monteria, capital city of the Department of Córdoba (Colombia). METHOD: The ethnographic analysis came from the postulates of Human Geography to interpret the historical and current meanings of Avenida Primera, covering both social uses and reforms it has had throughout time. RESULTS: The physical spaces of this Avenida, being inhabited by citizens, became social places full of history and meaning, where encounter and conflict , tradition and cultural renewal, diversity and search for identity, as well as struggles for sociopolitical recognition coexist. CONCLUSIONS: The research contributes to the studies on territory a socio-cultural perspective of urban construction conceiving them as dynamic social spaces rather than as static physical constructions. © Universidad de Caldas.